EVALUATION OF INCLUSIVE EDUCATION IN INDONESIA: ELEMENTARY SCHOOL TEACHERS' PERSPECTIVE - Iftita Rahmi; Erika Desvianti; Dian Mufitasari; Tika Dwi Ariyanti (Universitas Negeri Padang, 2024)
This quasi-qualitative study explored the concerns, barriers, and impacts of implementing Inclusive Education (IE) in elementary schools in Sumatra and Java, Indonesia. Despite the Indonesian government's mandate to implement IE through Ministry of Education Act No. 70 of 2009, various challenges hinder its effective implementation. A survey and semi-structured interviews were conducted with 25 elementary school teachers to gain insight into their experiences and perceptions of IE. The findings suggest that teachers often lack confidence in employing inclusive strategies because of limited knowledge and large class sizes, highlighting the need for ongoing professional development. Additionally, while there is evidence of positive attitudes towards special educational needs (SEN) students among peers and parents, teachers may not fully embrace IE. This study aims to provide a thorough assessment of IE strategies employed in Indonesian elementary schools by analyzing key factors and offering recommendations to enhance the effectiveness of IE for both students and teachers. These findings will inform policymakers, educators, and stakeholders about the current state of IE and the necessary steps to improve it, ultimately contributing to the development of a more inclusive and equitable education system in Indonesia.